Exploring English Majors’ Experience in Taking IELTS Speaking Practices: A Qualitative Study - Muliana Wahyuni Halid; Karmila Machmud; Abid Abid (Jambura Journal of English Teaching and Literature, 2022)
This study sought to explore the experience of students majoring in an English Department in taking the IELTS speaking practices, and whether or not they had challenges during the learning process. A qualitative approach was employed, and for collecting data a WhatsApp voice note application was utilized. Three students studying at a university in Gorontalo, Indonesia, agreed to participate voluntarily. The findings revealed that the students experienced different challenges during the IELTS speaking practices, which were grouped into five themes: (1) students prepared themselves in different ways, (2) students viewed IELTS differently, (3) students encountered some problems during the IELTS speaking practices, (4) students had issues in adjusting their answers to the test duration, and (5) students agreed that the IELTS test is important for their future. It was also found that the students still had challenges in practicing the IELTS speaking tests. For instance, they felt nervous, lacked English academic vocabulary, and even worried about using correct English grammar. The study recommends that students need to do more readings and spend a sufficient amount of time practicing with peers, so they could expand their knowledge and structure their responses well. In addition, lecturers can help students by giving authentic IELTS materials and visualizing the example of IELTS speaking tests in the classrooms.